2008
DOI: 10.2214/ajr.07.3006
|View full text |Cite
|
Sign up to set email alerts
|

MR Cholangiopancreatography with T2-Weighted Prospective Acquisition Correction Turbo Spin-Echo Sequence of the Biliary Anatomy of Potential Living Liver Transplant Donors

Abstract: Preoperative MRCP using a respiratory navigator-triggered T2-weighted TSE sequence with a PACE technique accurately depicts the biliary anatomy in LDLT donors and may guide intraoperative management of the biliary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
4
31
2
2
Order By: Relevance
“…However, conventional MRC could not accurately depict the second-order branches in every case. In a recent report, Basaran et al 46 used a T2-weighted prospective acquisition correction (PACE) technique turbo spin-echo (TSE) sequence. This technique allows good visualization of the peripheral intrahepatic biliary tree.…”
Section: Preoperative Donor Biliary Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional MRC could not accurately depict the second-order branches in every case. In a recent report, Basaran et al 46 used a T2-weighted prospective acquisition correction (PACE) technique turbo spin-echo (TSE) sequence. This technique allows good visualization of the peripheral intrahepatic biliary tree.…”
Section: Preoperative Donor Biliary Evaluationmentioning
confidence: 99%
“…47 Ramacciato et al 48 stressed that when isolating the hilar structures, the surgeon should isolate the right or left hepatic duct and transect it sharply to leave the peribiliary plexus an intact as possible to preserve the vascularization of the donor biliary system. Minimum dissection of bile duct around the hilum is 35 and Basaran et al 46 Type A 1 : right anterior (RA) hepatic duct (HD) and right posterior (RP) HD combine and form the right hepatic duct (RHD), and this duct combines with left (L) HD in the hepatic hilus. Type A 2 : common junction of RAHD, RPHD, and LHD.…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…high risk trifurcations (Smadja/Blumgart D1/D2 variants) with the cross over drainage of the right posterior/anterior duct into the left main hepatic duct likewise complex quadrifurcations (Smadja/Blumgart E1/E2 variants) in order to protect the donor from injuries and also to prevent dangerous biliary reconstructions in the graft which can result in postoperative bile leakage or anastomotic stricture [24]. During the donor operation (second step) an intraoperative cholangiography has been mostly performed prior to the transhilar passage in order to determine the transection line inside the corridor marked with a clip along the hilar plate inbetween the central-1° and right peripheral 2°/3° branching levels [13]. Therefore, a sufficient imaging allowing for the proper donor selection and reliably assisting the transhilar passage provides the 3-dimensional visualisation of the bile duct anatomy inside and outside the corridors but in topographical relation to the individual segmental liver make up [12].…”
Section: Discussionmentioning
confidence: 99%
“…They also found higher image quality for the 3D sequences without a difference concerning accuracy. The group of Basaran et al compared source and MIP images of a T2 TSE sequences and found no differences concerning specificity, sensitivity and positive as well as negative predictive values [13]. Lim et al analyzed MRCP for preoperative evaluation of PLLDs using 2D T2w MRC, 3D T2w MRC, and 3D contrast-enhanced T1w MRC [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation